Management of Katigraha Through Ayurveda – A Case Report: Life Sciences-Ayurveda - Bhoyar, Swapnil; Deshmukh, Dr. Sourabh; Thakre, Dr. Trupti; Khaire, Utkarsha (International Journal of Life Science and Pharma Research, 2023)
The description of Katigraha is not available as a separate entity in the classics. It is described amongst the eighty by Nanatmaja Vatavyadhi in the Charak Samhita. Ayurveda provides a horizon for such patients with its miraculous treatments of Panchakarma, Shamana, Rasayana, Agnikarma, etc. Lumbar canal stenosis is an abnormal narrowing of the spinal canal in the lumbar region, resulting in a neurological deficit that produces symptoms like pain, numbness, paraesthesia, and loss of motor function. Abnormal weight distribution combined with soft tissue laxity and instability over a prolonged period allows for excessive joint play and buckling of the posterior annular fibres of the intervertebral disc (IVD). The main treatment protocol, according to Ayurveda, is the use of both purification and palliative treatment. This case report represents a 56-year-old male patient who came to the OPD complaining of pain in his lumbar, hip, and legs; tingling sensation; stiffness; and walking difficulty. At Kati Pradesh, the trauma caused by the fall led to the vitiation of Vata and kha- vaigunya. Additionally, Agnimandya was already there, which caused ama to develop. He was given both Shodhana and Shamana Chikitsa. There was a significant improvement in the symptoms, and the patient could do his routine work without any support. This case and its results show that this therapy is effective in lumbar canal stenosis and should be done in a large population. Patients with lumbar canal stenosis can be effectively treated with Panchkarma procedures and oral medications without surgical intervention.